2016
DOI: 10.1055/s-0036-1592709
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BRCA1 promotor hypermethylation in recurrent high grade ovarian cancer

Abstract: Background: Approximately 20-25% of ovarian cancers are attributable to germline or somatic BRCA1/2 mutations, resulting in defects in the homologous recombination pathway. Inactivation of these genes can also be mediated by epigenetic changes, e.g., hypermethylation of CpG islands in the promoter regions. In such homologous recombination deficient tumors, platinum based chemotherapy is in general effective, however, loss of hypermethylation might lead to refractory disease. The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Moreover, tissue sampling size and content introduces bias owing to variations in sampling sites (ovary versus metastatic), neoplastic cell content and intratumor heterogeneity. Four studies report particularly high BRCA1 methylation rates: 21.4% 35 , 33.6% 16 , 42% 39 and 73.7% 43 . This latter cohort, which confirmed all its MSP-GE determined BRCA1-methylated OC cases with Sanger sequencing, consisted solely of relapsed cases, which may account to some extent for this variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, tissue sampling size and content introduces bias owing to variations in sampling sites (ovary versus metastatic), neoplastic cell content and intratumor heterogeneity. Four studies report particularly high BRCA1 methylation rates: 21.4% 35 , 33.6% 16 , 42% 39 and 73.7% 43 . This latter cohort, which confirmed all its MSP-GE determined BRCA1-methylated OC cases with Sanger sequencing, consisted solely of relapsed cases, which may account to some extent for this variation.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, chemotherapy induces changes affecting the methylation levels of the BRCA1 promoter, causing earlier and perhaps more frequent resistance to platinum-based chemotherapy than is observed in BRCA1-mutated OC. This may manifest as methylation loss in relapsed BRCA1-methylated OC, observed in 16.7% -80.0% of small mostly retrospective cohorts of 6 to 13 paired primary/recurrent BRCA1-methylated HGSC 43,52,54,55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many recent studies do not support these findings [20][21][22][23] . In some cases, methylated BRCA1 in tumors was found to be demethylated after chemotherapy 24,25 . The presence of BRCA1 methylation before treatment was associated with post relapse platinum resistance in a study of triple-negative breast cancer 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although hypermethylation of the BRCA1 promoter has been shown in xenografts to predict response to PARP inhibitors as well [8], data on patient survival are still unclear [9]. Recently, we showed that the BRCA1 promoter is frequently hypermethylated in ovarian cancer tissue, but the methylation status is often lost in recurrent disease, suggesting a potential resistance mechanism either through therapy-induced cancer evolution or by clonal selection [10][11][12]. Thereby, the detection and monitoring of BRCA1 promoter hypermethylation may have an important impact on the clinical management of ovarian cancer patients without BRCA1 mutation [8].…”
Section: Introductionmentioning
confidence: 99%